MIKROFASIES BATUGAMPING FORMASI BULU DAN KUALITAS BAHAN BAKU SEMEN, PADA LAPANGAN GUNUNG “PAYUNG”, KECAMATAN BOGOREJO, KABUPATEN BLORA JAWA TENGAH - Ajidityo Putro Fadhlillah; Yoga Aribowo; Dian Agus Widiarso (Geological Engineering E-Journal, 2014)
Bulu Formation is one of formation which is sedimented at Tertiary age in The North East Java Basin. Bulu Formation has a lithological composition of limestones with kalkarenit. Bulu Formation is located in Gandu village, Tahunan Village, and the surrounding areas, District Bogorejo, Blora, Central Java, with a particular study on the "Gunung Payung".The study aimed to determine microfasies, facies zone, the relative age, and standart of quality limestone as materials cement on data petrographic, paleontologist, and chemical analysis of limestone samples in the study area. Development of Limestone Bulu Formation Unit microfacies is Bioclast Red Algae Packstone, Bioclast Large Foram Grainstone, Bioclast Large Foram Packstone, Bioclast Planktonic Foram Packstone, Bioclast Grainstone with dolomitation, Planktonic Forams Grainstone, Planktonic Wackstone, Peloidal Wackestone, Packstone with dolomitation, Bioclast Wackstone with microspar, Bioclast Planktonic Foram Wackstone, Bioclast Wackstone with dolomitation, Bioclast Packstone with dolomitation, and Dolomite limestone.Based on the analysis microfacies and foraminifera on the areas of research, there are 3 types of facies zoning based on the model of Wilson (1975), namely: FZ 5 Platform - Margin Reefs, Marine Open 7 FZ, FZ 8 Platform and Interior - Restricted to the age of rocks between N9 to N12 is the Middle Miocene. From the chemical analysis, the potential limestones in the study area can be used as raw material for cement and relationships microfacies analysis and chemical analysis showed that the pitch "Gunung Payung" has a great potential in terms of good quality which is spread of West to East direction. The west area of “Gunung Payung” has better quality of limestone as a raw material for cement than east area.